Cross-sex hormone therapy in rats induces sex-specific adaptations of renal function and sodium transporters expression - Lichtenecker, Debora Conte Kimura; da Silva, Nathalia Beserra; Silveira, Isabela Borges; Monteiro, Letícia Maria; Argeri, Rogerio; Dias Da Silva, Magnus R.; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2025)
IntroductionCross-sex hormone therapy (CHT) has been used in the gender identity-affirming process. Nevertheless, the literature about the renal repercussions of this therapy is scarce.ObjectiveEvaluate the effects of CHT on blood pressure (BP) and renal function.MethodsMale and female Wistar rats were distributed into groups: M + H (male + hormone), M + V (male + vehicle), F + H (female + hormone), and F + V (female + vehicle). CHT: M + H received algestone-acetophenide (3 mg/kg) plus estradiol-enanthate (0.18 mg/kg); F + H, testosterone-cypionate (3 mg/kg). The vehicle was sesame oil. After 2 months of treatment, BP and renal function [inulin clearance (GFR), ions, and acid excretions] were evaluated. Sodium transporters expression (NHE3, NCC, α-ENaC, and β-ENaC) was assessed by immunohistochemistry.ResultsCompared to M + V, M + H presented reduction in BP and GFR but increase in sodium and potassium excretion. GFR did not change in F + H, but sodium and potassium excretions were reduced. Ammonium excretion was decreased in M + H but increased in F + H. The NHE3 expression decreased in M + H and increased in F + H; females showed higher expression of NCC, while CHT did not change it. The β-EnaC expression was higher in females; CHT increased it in males and females.ConclusionCHT induces sex-specific renal adaptations. Testosterone in females reduces the excretion of sodium and other ions, which may predispose to hypertension. Conversely, estradiol + algestone in males decrease the glomerular filtration rate and alter sodium handling, suggesting maladaptive responses. The expression of sodium transporters was altered in a sex- and nephron segment-specific manner. These findings highlight the need for further studies on the renal consequences of hormone therapy in transgender individuals.